2016
DOI: 10.1021/acs.bioconjchem.6b00629
|View full text |Cite
|
Sign up to set email alerts
|

Simple Strategy for Taming Membrane-Disrupting Antibiotics

Abstract: A strategy has been devised for increasing the cellular selectivity of membrane-disrupting antibiotics based on the attachment of a facially amphiphilic sterol. Using Amphotericin B (AmB) as a prototype, covalent attachment of cholic acid bound to a series of α,ω-diamines has led to a dramatic reduction in hemolytic activity, a significant reduction in toxicity toward HEK293T cells, and significant retention of antifungal activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…These contrast functional outcomes at low and high concentrations are predicted to undergo in vivo , which is unique for AM3. This feature may contribute development of anti-fungal compounds having less side effects 42 44 .…”
Section: Discussionmentioning
confidence: 97%
“…These contrast functional outcomes at low and high concentrations are predicted to undergo in vivo , which is unique for AM3. This feature may contribute development of anti-fungal compounds having less side effects 42 44 .…”
Section: Discussionmentioning
confidence: 97%
“…An entirely different approach that we have devised for improving the selectivity of membrane-disrupting antimicrobial agents in general, and for Amphotericin B in particular, is to reduce the hemolytic activity of aggregated forms via a “taming” strategy [ 28 , 29 ]. In Figure 7 an illustration is shown of our taming concept.…”
Section: Discovery Of a Membrane Rupture And Leakage Dichotomymentioning
confidence: 99%
“…For proof of concept, we synthesized a series of conjugates of Amphotericin B bearing one, and also two, choloyl moieties. In Figure 8 , it is shown that the simplest representative examples in which Amphotericin B has been covalently attached to a single choloyl group using four different spacers, i.e., 2a – d [ 29 ].…”
Section: Discovery Of a Membrane Rupture And Leakage Dichotomymentioning
confidence: 99%
See 2 more Smart Citations